Farming system and cultivation constraints in African yam Dioscorea dumetorum (Pax, Kunth) production in Benin. - ADOUKONOU-SAGBADJA, Hubert (My University, 2020)
Dioscorea dumetorum is one of the important cultivated yams that significantly contribute to food security and poverty alleviation in Benin. However, the potential of this tuber crop is under-exploited and its production completely neglected by research and development policies. The objective of this study was then to document the indigenous knowledge related to its traditional farming system, agronomic practices and constraints that limit its production in Benin. Therefore, an ethnobotanical survey was conducted in seventy-eight (78) villages covering the major production areas in the country. The results revealed that D. dumetorum cultivation was mainly traditional and dominated by male, adults and old farmers while the participation of youth and women was found minimal. According to farmers, this yam was a less-demanding crop, requiring no specific input. Four main cropping systems practiced by farmers were identified. These were crop-association (50.53% of respondents), monoculture (20.47%), crop-rotation (18.86%) and home gardens planting (10.14%). Besides, seven approaches (use of basket, garret, straw hut, bag, shade, hole and pile) were practiced for postharvest storage of tubers. Finally, diverse range of constraints, including the susceptibility of tubers to termites and rodents in storage or in late harvesting, the frequent occurrence of drought during sprouting time, tubers’ hardening in storage making them unsuitable for pounding, the presence of roots on tubers, were reported to impede D. dumetorum production. The important ethnobotanical data recorded here are useful for breeding programs but also in defining appropriate strategies for conservation and valorization of D. dumetorum in Benin.
Keywords: Benin; constraints; D. dumetorum; production system; storage; yam.